Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.2343/geochemj.40.33
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical signatures preserved in ancient siliceous sediments; new perspectives to Triassic radiolarian bedded chert compositions

Abstract: Major and minor elements of successively collected 70 Middle Triassic radiolarian bedded cherts from the Mino Belt in central Japan were studied. In order to reveal pre-diagenetic, primary geochemical signatures related to marine biogeochemical cycles, composite data of chert-shale couplets in addition to raw data were examined. The results show that Mn, Cu, Sr, Ba and P were supplied significantly by non-lithogenic excess fractions. Positive correlation with SiO 2 / TiO 2 suggests that accumulations of Ba, Sr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 68 publications
(88 reference statements)
1
13
0
Order By: Relevance
“…Behavioural avoidance of acid sulfate soils has been shown in juveniles of various fishes when pH levels were well within the range exhibited in natural systems (Kroon 2005). Red soil in Okinawa is acidic, with a pH of ~5 (Mkadam et al 2006), and analysis of the rearing conditions used here showed that the pH decreased with both increasing concentration of red soil and time. Reductions in pH of a similar magnitude (0.07) were shown to elicit similar behavioural changes in juvenile coral trout (Plectropomus leopardus) (Munday et al 2013).…”
Section: Discussionsupporting
confidence: 63%
“…Behavioural avoidance of acid sulfate soils has been shown in juveniles of various fishes when pH levels were well within the range exhibited in natural systems (Kroon 2005). Red soil in Okinawa is acidic, with a pH of ~5 (Mkadam et al 2006), and analysis of the rearing conditions used here showed that the pH decreased with both increasing concentration of red soil and time. Reductions in pH of a similar magnitude (0.07) were shown to elicit similar behavioural changes in juvenile coral trout (Plectropomus leopardus) (Munday et al 2013).…”
Section: Discussionsupporting
confidence: 63%
“…Most of these oxides had positive correlations among them. In particular, the correlation coefficient between P 2 O 5 and CaO was the highest and positive (r = 0.90), which indicates that the two oxides are mainly derived from apatite (Takiguchi, Sugitani, Yamamoto, & Suzuki, ). After correcting contribution from apatite, the correlation coefficients of CaO* with Al 2 O 3 and K 2 O (r = 0.33 and 0.56) became higher than those of CaO (r = 0.18 and 0.50) except for that with Na 2 O, whereas that with P 2 O 5 (r = 0.64) became lower than that of CaO.…”
Section: Resultsmentioning
confidence: 96%
“…The accretion rate of spherules is controlled by the sediment accumulation rate for shale and chert beds. Sedimentological and geochemical studies have suggested that the present alternations of chert and shale beds refl ect original cyclic sedimentation of siliceous and relatively clay-rich materials (Hori et al, 1993;Takiguchi et al, 2006), though probably biased and exaggerated by later diagenetic redistribution of Si (Tada, 1991). Although there is no direct estimation of accumulation rates on individual shale and chert beds, Hori et al (1993) suggested that the shale bed has a much slower accumulation rate than the chert bed, based on the 10-100 times higher abundance of magnetic microspherules of probable extraterrestrial origin in shale than in chert.…”
Section: Middle Triassic Micrometeoritesmentioning
confidence: 98%